Cultivating Generation Z's Sense of Nationalism in the Era of Globalization Through the Implementation of Pancasila - Ariyanti, Salsa; Hawa, Gita Ismatul; Ardiyanti, Diana Kumala; Sami'an, Sami'an (PT. Civil Military Center, 2025)
Indonesia has a variety of languages, religions, tribes, and races as national characteristics. This diversity must be managed seriously by the young generation of the Indonesian nation. However, in the midst of this era of globalization, the young generation must face major challenges in managing the existing diversity, challenges in maintaining a sense of nationalism amidst the current of globalization that is starting to spread widely among the community. Because the sense of nationalism plays a very important role in uniting the differences in diversity that exist. The spread of the current of globalization has resulted in a sense of nationalism around society decreasing, especially for generation Z. The cause of the decline is the entry of foreign cultures into a country that is considered more modern and attractive because it is in accordance with the development of the times. Therefore, efforts are needed to maintain and foster a sense of nationalism in generation Z, by introducing a variety of Indonesian cultures, loving domestic products and cultures, implementing Pancasila in everyday life, and being more selective about the presence of foreign cultures into the country. Therefore, this study aims to determine the application of Pancasila in terms of fostering a sense of nationalism for generation Z in the era of globalization. The method used in this study is a qualitative method, namely a method whose discussion theory is obtained from various sources such as journals, books, and articles. The results of the study indicate that the application of Pancasila is very important in fostering a sense of nationalism in generation Z, because generation Z is very easily influenced by foreign cultures. The application of Pancasila can be carried out starting from elementary school to college through Pancasila education, where in Pancasila education studying Pancasila which is the basis of the Republic of Indonesia which can be used as a foundation for generation Z in fostering a sense of nationalism.